PEMBUATAN SISTEM INFORMASI PENGAJIAN PEGAWAI BERBASIS WEB DI INSTANSI XYZ - Seliwati, Seliwati; Alfansyah, Renaldi Fajar (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Management of data administration staffing within an organization or institution holding the role is important in the process of administration. In the case of this system of administration personel be one of the factors which affect the agency staffing and training regency XYZ thus greatly expected to process management administration employment in the service of the filing can be done with quickly and efficiently with the web based staffing administration system design can facilitate the admin in inputting administration data reducing the time that is quite long minimize the possibility of errors in recording and speed up the search process. Manage administration submission data through the process of filing the administration that can generate a report and letter of introduction storing the data administration to the MySQL database is easy and fast at the same securing the data administration of the order not be accessible to all people.